Chemical composition and antibacterial activity of essential oil from leaves and twigs of Pistacia lentiscus growing in Mostaganem Province (Algeria) - Arabi, Abed; Djibaoui, Rachid; Malihac, Catherine; Lattab, Aicha; bechelaghem, Nadia; Dahah, Hichem (My University, 2017)
This study was designed to examine the chemical compositionand the antibacterial activity of essential oil of Pistacia lentiscus (Anacardiaceae) from Mostaganem province (northwest of Algeria).Oil was obtained using the hydrodistillation method (Clevenger type) and subsequently analyzed by Gas Chromatography–Mass Spectrometry (GC–MS). The in vitro antimicrobial activity against some clinical pathogens was evaluated using the agar diffusion method, the minimum inhibitory concentrations (MIC) were also determined against the same microorganisms using the microdilution method.Among the 50 constituents identified (representing 99.9% of the oil composition) of which the monoterpene hydrocarbons are the dominated (72.43%); α-pinene (42.13%), sabinene (6.46%), ɣ-terpinene (6.21%) et α-terpinolene (2.18%) being the main components.Antimicrobial activity revealed that the essential oil had promising anti-microbial effects against several multiresistant bacteria, giving satisfactory zone diameter values (40.00, 24.71, 24.60, 23.54, 16.07, 14.58 and 12.86 mm) and MIC values (0.05, 0.1, 0.1, 0.2, 0.2, 0.2 and 0.1%) forgram-negative bacteria: Helicobacter pylori, Escherichia coli, Morganella morganii, Enterobacter cancerogenus and Serratia fonticolaand gram-positive bacteria: Staphylococcus aureus and Enterococcus faecalis, respectively
Keywords: Pistacia lentiscus, Essential oil, Chemical composition, Antimicrobial activity